E0486 Transcatheter closure of no rim large atrial septal defect with amplatzer occluders: technical considerations, safety and feasibility. (17th November 2010) - Lianglong, Chen; Yukun, Luo; Chaogui, Lin; Yafei, Peng; Xingchen, Zheng
Abstract : Backgrounds: Transcatheter closuring no rim or large atrial septal defect (ASD) with Amplatzer occluding device (AOD) was technically challenged. The present study was to address technical issues, and to test the safety and feasibility for transcatheter closuring large and no rim ASDs with AOD. Methods: Patients, with large ASDs of 325 mm and with no rims at least in one defect border detected echocardiographically, were included in the study. 49 patients eligible underwent transcatheter closure of ASDs and divided into group A (n=26, large ASDs with intact rims) and group B (n=23, large ASDs with no rims). Three occluding methods i.e. the conventional releasing, the waist pre-releasing, and the dumbbell-shaped releasing were sequentially attempted for all patients if necessary. For the waist pre-releasing method, the waist of AOD was released immediately following the expansion of the distal umbrella and withdrawn to wedge the defect in order to enhance the self-centralisation of the occluder; for the dumbbell-shaped releasing method, the distal umbrella was released within the upper left pulmonary vein to constrain the expansion of the umbrella, and the delivering catheter was further withdrawn slowly until the proximal umbrella was expanded in the right atrium, and finally, the original shape of the distal umbrella could quickly recover by slightly shaking or pulling the catheter, meanwhile the AOD could well fixed the defect. Results: The average diameter of ASDs in group A and B were 27.2±11.7 mm and 28.5±11.9 mm, respectively (p>0.05), and the average diameter of finally used AODs was 34.5±10.2mm and 38.7±11.9 mm, respectively (p<0.01). The technical successful rates respectively for group A and B were 61.5% and 26.1% (p<0.05) by using the conventional releasing method, increased to 70.1% and 39.1% (p<0.05) by trying the waist pre-releasing method, and further increased to 100% and 100% by attempting the dumbbell-shaped releasing method. Neither major complications no occluder dislodging occurred peri-procedurally in the two groups. Conclusions: Trans-catheter closure of no rim large-to-huge ASD with the AOD may be safe and feasible; closuring no rim large-to-huge ASD needs bigger AODs and more use of the dumbbell-shaped releasing method.